ARTIFICIAL INTELLIGENCE IMPLEMENTATION IN EDUCATION SYSTEMS: A GLOBAL BIBLIOMETRIC ANALYSIS - Syaifullah Syaifullah; Nurjannah Nurjannah; Mei Hastuti; Hirma Hirma; Nur Hadisa (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study explores the dynamic development of artificial intelligence (AI) implementation in education, with a particular focus on bibliometric trends of scholarly articles indexed in Scopus between 2022 and 2025. Using a quantitative approach, bibliometric analysis was conducted through Biblioshiny (R-package), VOSviewer, and Publish or Perish, with data selection guided by the PRISMA framework. After applying strict inclusion criteria, 784 eligible articles were analyzed. Results indicate a strong annual publication growth rate of 47.83%, with the United States and Hong Kong emerging as the leading contributors in terms of both volume and citation impact. Dominant keywords include ChatGPT, higher education, and generative AI, showing current research priorities. Influential journals such as Computers and Education: Artificial Intelligence and Education and Information Technologies significantly shape the field. Thematic mapping reveals that while core topics are well established, areas such as AI ethics and teacher preparedness remain underexplored. This study offers a comprehensive overview, highlights research gaps, and suggests future directions to advance AI integration in education. The findings provide practical guidance for educators, institutional leaders, and policymakers in prioritizing AI adoption, strengthening teacher capacity, and developing ethical frameworks to support sustainable AI integration within education systems.